UTILIZING TECHNOLOGICAL AIDS IN ENGLISH LANGUAGE LEARNING - Henny Mardiah (LP2MTBM MAKARIOZ, 2019)
In this globalization era, the advancement of technology is growing rapidly day by day, unstoppable. Technology helps people to simplify their works. Many aspects of life have been positively affected by current technology. Technology becomes the normal and expected means of communications and education. In English Language Learning, the latest technology such as computers, the internet, electronic dictionary, email, blogs, mobile phones, online course may promote English use wider. Moreover, it is seen as the tools to promote autonomous learning. The emerging current technology creates new teaching model, in which technology-based activities are seen as more effective, efficient, engaging and enjoyable in classroom practices. This research is aimed to analyze the application of current media and elaborate challenges faced by utilizing these technologies. This study also raises teacher’s awareness in using them effectively. Trained teachers are needed to apply this new teaching model successfully. Most importantly, by integrating technological aids as classroom media will surely motivate students’ interests to learn and communicate English in their daily interactions.